Morphological And Molecular Analysis Of Penaeus Semisulcatus From The Persian Gulf And Oman Sea - ahromi, Saeid Tamadoni J (2011)
There are two morphotypes of the green tiger shrimp, Penaeus semisulcatus recognized in the Persian Gulf and Oman Sea. The two morphotypes are distinguished by colour pattern of antenna and body transverse lines. This study is conducted to investigate the taxonomic status of the two morphotypes based on morphometrics and mitochondria DNA sequence analysis. In addition, population genetics study on P. semisulcatus from the Persian Gulf was performed to assist the selection of suitable broodstocks in future breeding programs. A total of 25 characters were investigated for morphometric study. Ten of these characters showed significant differentiation between single sex and combined sex (P < 0.05).